Properties of plasma sprayed ScSZ electrolyte coating. Issue 5 (September 2012) - Aruna, Singanahally T.; ShriPrakash, Badi; Balaji, Narayanaswamy; Grips, Vatia K. W.
Abstract : The cost-effective preparation of solid oxide fuel cell (SOFC) electrolyte layer is an important issue for its practical application to SOFCs. Among many processes used for preparing electrolyte in SOFCs, atmospheric plasma spraying is of advantage because of rapid deposition with flexibility possibly leading to cost-effective manufacturing of SOFCs. In the present study, plasma-sprayable scandia-stabilized zirconia (ScSz) powder is prepared by co-precipitation route without any agglomeration step and the powders are characterized for phase, morphology, flowability and particle size using powder X-ray diffractometry, Raman spectroscopy, field emission scanning electron microscopy, Hall flow meter, and particle size analyzer. The powder exhibited cubic phase, good flowability, and blocky angular shape. Free-form of plasma sprayed ScSZ is characterized for conductivity. The overall conductivity of ScSZ plasma sprayed coating at 773 K (∼7.19 × 10−4 S/cm) is much higher than the reported value at the same temperature for plasma sprayed ScSZ. This may be due to the better melting of the particles in the present study. The as plasma sprayed coating is also characterized by field emission scanning electron microscopy to determine the adhesion of the coating to the substrate.